A Case Report of Late-Onset and Pregnancy-Related Tufted Angioma in Thailand - Pongchomporn, Monsiya; Pattamadilok, Bensachee (Thai Journal of Dermatology, 2016)
Tufted angioma is a rare benign vascular tumor of the skin, usually occuring during infancy or childhood by either congenital or acquired causes. Adult onset has rarely been reported and pregnancy-related incidences are also infrequent. However, we reported a Thai woman with adult-onset, pregnancy-related tufted angioma. Such a case has seldom been seen in Thailand or even in world-wide medical literature. In our case, the patient presented with a slowly progressing lesion with tender, dull erythematous macules and papules which coalesced into patches and plaques with a mottled appearance on the right inframammary area. The lesion began when she was in the seventh month of pregnancy. She was later treated with vascular laser with excellent results.